Metavac-RSV mucosal bivalent vaccine candidate protects cotton rats against pneumoviruses and is produced using serum-free cell culture in bioreactor - Caroline Chupin; Pauline Brun; Marjorie Ray; Chloé Mialon; Maëlle Reitano; Aurélien Traversier; Emilie Laurent; Abdelghafar Goumaidi; Julien Fouret; Stéphane Paul; Marina Boukhvalova; Kevin Yim; et al. (npj Vaccines)
Abstract Respiratory syncytial virus (RSV) and human metapneumovirus (HMPV) are the main etiologic agents of viral bronchiolitis and pneumonia in children and the elderly. As live-attenuated vaccines (LAV) can stimulate robust mucosal and cellular responses, we previously engineered an HMPV-based bivalent LAV Metavac®-RSV candidate and reported its capacity to protect mice against HMPV and RSV challenges after intranasal delivery. To progress towards clinical development, we identified a GMP-grade Vero cell platform as permissive and efficient to produce high yields of functional Metavac®-RSV, expressing both RSV and HMPV F antigen after several passages. Metavac®-RSV protected cotton rats against both HMPV and RSV challenges, significantly reducing viral replication in the respiratory airways and inducing high titers of neutralizing antibodies. Finally, we identified process parameters to scale-up the production process of Metavac®-RSV using Vero cells cultivated on microcarriers in a 2 L single-use stirred-tank bioreactor, with a scalable upstream production process amenable to industrial manufacturing.